2009
DOI: 10.1002/mds.22612
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine and cardiovascular responses to maximal exercise in Parkinson's disease on and off medication

Abstract: The aim of this experiment is to understand how Parkinson's disease (PD) medication affects the autonomic responses of individuals during an acute exercise stress test. Fourteen people with PD and fifteen healthy individuals age-matched between 50 and 80 years performed a modified Bruce protocol. Subjects with PD performed the test once off medication (PD-off) and then 1 week later on medication (PD-on). Heart rate (HR), blood pressure (BP), VO(2), and norepinephrine (NE) levels were taken at rest and at peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 20 publications
3
55
0
Order By: Relevance
“…The authors comment that it may be difficult to attain an exercise intensity high enough to trigger ROS in order to show changes in the antioxidant defense system. In our most recent experiment, subjects with PD, both on and off medication, exercised to the same peak VO 2 as our healthy controls demonstrating that this population is capable of attaining the same intensity as healthy peers [29].…”
Section: Discussionmentioning
confidence: 52%
“…The authors comment that it may be difficult to attain an exercise intensity high enough to trigger ROS in order to show changes in the antioxidant defense system. In our most recent experiment, subjects with PD, both on and off medication, exercised to the same peak VO 2 as our healthy controls demonstrating that this population is capable of attaining the same intensity as healthy peers [29].…”
Section: Discussionmentioning
confidence: 52%
“…In the few previous studies that have examined the hemodynamic responses to exercise in Parkinson's, the blood pressure responses to maximal exercise were reduced [6,7,8] and the pressor responses to sub-maximal exercise were preserved in Parkinson's patients [9,11]. In the former studies the integrity of autonomic function of the patients was not reported and the reduced blood pressure response may have been a result of the lower aerobic capacity and peak power output achieved.…”
Section: Discussionmentioning
confidence: 97%
“…The blood pressure responses to e er ise i Parki so 's disease ha e ee s ar el i estigated ho e er. The few previous studies that have been conducted have shown that the pressor response to maximal exercise is blunted and that aerobic capacity is reduced in Parki so 's patients [6,7,8]. The integrity of the autonomic nervous system in those studies was not reported however, thus it was unclear if the reduced pressor response in those patients was due to autonomic dysfunction and/or another mechanism(s).…”
Section: Introductionmentioning
confidence: 97%
“…Sessions consisted of 20 min of aerobic training either using a treadmill (Cybex, Landice 8700, Medway, Mass., USA) or a Stairmaster 4000PT (Brooklyn, N.Y., USA). Exercise intensity was monitored to maintain a heart rate consistent with 60-70% of max VO 2 (as determined by the exercise stress test) [21,22] . Weight training consisted of 5 Cybex resistance exercise machines: leg extension, leg curl, leg press, arm curl, and chest fly.…”
Section: Vitamin Supplementation Groupmentioning
confidence: 99%
“…The combination of aerobic exercise and strength training has been shown to be optimal for increasing GSH in the obese and in healthy older adults [19,20] . In individuals with PD, exercise has also been strongly recommended for reasons not directly related to reducing oxidative stress (mobility, functional performance, cardiovascular and respiratory complications) [4,[21][22][23] . The impact of exercise on homocysteine and GSH levels in PD has never been examined.…”
Section: Introductionmentioning
confidence: 99%